Carmilla : A Critical Edition - Le Fanu, Joseph Sheridan, 1814-1873 (Book collections on Project MUSE., 2013)
Text of and critical essays on the 1872 vampire tale chronicling the experiences of a young woman lured by the charms of a female vampire.